FAKTOR KETIDAKPATUHAN TERKAIT ATURAN PELAPORAN DANA KAMPANYE TERHADAP AKTIVITAS PEMILU PARTAI C DI KABUPATEN TULUNGAGUNG - Niken Ayu Sastie; Hero Priono (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
This study aims to analyze the factors that cause Party C's non-compliance in reporting campaign funds during election activities in Tulungagung Regency. This study examines the factors contributing to the lack of transparency of campaign finance reporting, as well as the impact of non-compliance on the integrity of the electoral process. The analysis is based on a descriptive qualitative approach, using data from various sources, including campaign finance reports, and interviews with election participants. In addition, weak oversight and perceived ineffective sanctions contribute to the low level of compliance. This study suggests the need for simplification of reporting rules, increased education and training programs, stricter supervision, and more severe sanctions to improve compliance and maintain the integrity of the electoral process in Tulungagung Regency.